Diffraction-limited imaging with monolayer 2D material-based ultrathin flat lenses - Lin, Han (2021)
Ultrathin flat optics allow control of light at the subwavelength scale that is unmatched by traditional refractive optics. To approach the atomically thin limit, the use of 2D materials is an attractive possibility due to their high refractive indices. However, achievement of diffraction-limited focusing and imaging is challenged by their thickness-limited spatial resolution and focusing efficiency. Here we report a universal method to transform 2D monolayers into ultrathin flat lenses. Femtosecond laser direct writing was applied to generate local scattering media inside a monolayer, which overcomes the longstanding challenge of obtaining sufficient phase or amplitude modulation in atomically thin 2D materials. We achieved highly efficient 3D focusing with subwavelength resolution and diffraction-limited imaging. The high focusing performance even allows diffraction-limited imaging at different focal positions with varying magnifications. Our work paves the way for downscaling of optical devices using 2D materials and reports an unprecedented approach for fabricating ultrathin imaging devices.